Impact of different doses of rivaroxaban on clinical outcomes in elderly patients with non-valvular atrial fibrillation: a real-world study - Yu, Juan; Zhang, Zufeng; Yuan, Qingru; Hu, Haobing; Li, Huimin; Huang, Meifang; Mao, Youlin (Frontiers in Pharmacology, 2025)
IntroductionThis study to assess the associations between different rivaroxaban doses and clinical outcomes in elderly NVAF patients in a real-world setting, and to explore factors influencing dose selection.MethodsA retrospective analysis was conducted on elderly patients (aged ≥65 years) diagnosed with NVAF and hospitalized at the Ninth People’s Hospital of Zhengzhou between 1 January 2022, and 31 December 2022. All patients received rivaroxaban therapy. Based on the prescribed dose, patients were categorized into a standard-dose group (15–20 mg/day) and a low-dose group (10 mg/day) groups based on the prescribed dose. Clinical outcomes within 12 months post-discharge were collected via follow-up, including readmission records and telephone interviews.ResultsA total of 214 elderly patients with NVAF were included in the study. The mean age was 79.2 ± 8.2 years in the low-dose group and 75.4 ± 8.0 years in the standard-dose group (P = 0.001). There were no significant differences were observed between the two groups in terms of sex (P = 0.298), CHA2DS2-VASc score (P = 0.783) and HAS-BLED score (P = 0.586). The low-dose group had a significantly higher proportion of older patients (P = 0.001) and individuals with a history of bleeding (21.42% vs. 7.79%, P = 0.004). Follow-up revealed no statistically significant differences between the two groups in thromboembolic events (P = 0.308) and bleeding events (P = 0.187). However, the standard-dose group had a higher 12-month cumulative survival rate (HR = 0.61; 95% CI: 0.39–0.95; log-rank; P = 0.03). After propensity score matching to balance baseline features, there was no difference between the two groups. Multivariate logistic regression analysis identifiedthe following as significant factors influencing dose selection: age (OR = 0.95, 95% CI: 0.91–0.98, P = 0.004), history of bleeding (OR = 0.36, 95% CI:0.14–0.95, P = 0.038), and estimated glomerular filtration rate (eGFR) (OR = 0.99, 95% CI: 0.97–1.00, P = 0.019).ConclusionThis retrospective study found that low-dose rivaroxaban was not significantly different from the standard dose in terms of thromboembolic events, bleeding, and all-cause mortality in elderly patients with NVAF. Although the safety profiles appeared similar between the two groups, the standard dose was associated with a higher cumulative survival rate in the unadjusted analysis. However, this observed survival difference may be influenced by baseline confounders, such as age and bleeding history. These findings suggest an association and support the need for further investigation into flexible anticoagulation strategies in clinical practice. Age, bleeding history, and renal function must be carefully considered when individualizing treatment.